Visible-light-driven proton reduction for semi-hydrogenation of alkynes via organophotoredox/manganese dual catalysis. Issue 55 (19th December 2022) - Wang, Xiao-Yu; He, Yong-Qin; Wang, Mei; Zhou, Yi; Li, Na; Song, Xian-Rong; Zhou, Zhao-Zhao; Tian, Wan-Fa; Xiao, Qiang
Abstract : An unprecedented protocol of visible-light-driven, organophotoredox/Mn dual catalyzed proton reduction for stereoselective semi-hydrogenation of alkynes is established. Abstract : Described here is a unprecedented organophotoredox/manganese dual catalyzed proton reduction and its application for semi-reduction of alkynes. The catalytic active pre-catalyst [Mn-1] can be feasibly be prepared on gram-scale from Mn(acac)2 ·2H2 O in air. This dual catalytic protocol features noble-metal-free catalysts, simple ligand, and mild conditions. Besides, a unique ortho -halogen and -hydroxyl effect was observed to achieve high Z -stereoselectivity.